Adeno-associated virus capsid antigen presentation is dependent on endosomal escape - Li, Chengwen (American Society for Clinical Investigation, 2013)
Adeno-associated virus (AAV) vectors are attractive for gene delivery-based therapeutics, but data from recent clinical trials have indicated that AAV capsids induce a cytotoxic T lymphocyte (CTL) response that eliminates transduced cells. In this study, we used traditional pharmacological agents and AAV mutants to elucidate the pathway of capsid cross-presentation in AAV-permissive cells. Endosomal acidification inhibitors blocked AAV2 antigen presentation by over 90%, while proteasome inhibitors completely abrogated antigen presentation. Using mutant viruses that are defective for nuclear entry, we observed a 90% decrease in capsid antigen presentation. Different antigen presentation efficiencies were achieved by selectively mutating virion nuclear localization signals. Low antigen presentation was demonstrated with basic region 1 (BR1) mutants, despite relatively high transduction efficiency, whereas there was no difference in antigen presentation between BR2 and BR3 mutants defective for transduction, as compared with wild-type AAV2. These results suggest that effective AAV2 capsid antigen presentation is dependent on AAV virion escape from the endosome/lysosome for antigen degradation by proteasomes, but is independent of nuclear uncoating. These results should facilitate the design of effective strategies to evade capsid-specific CTL-mediated elimination of AAV-transduced target cells in future clinical trials.